2021
DOI: 10.3390/ma14206092
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Biocomposites Produced with Thermoplastic Starch and Digestate: Physicochemical and Mechanical Characteristics

Abstract: This paper presents the results of a study on the influence of the addition of digestate (DG) sludge from an agricultural biogas plant on the mechanical properties of the coating obtained from thermoplastic starch (TPS). The dried, fragmented digestate, some of which had previously undergone ultrasound treatment, is used in the study. Biocomposites are produced by the pouring method using Teflon moulds as matrices. The physicomechanical study included the determination of the basic parameters of the materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
1
13
1
Order By: Relevance
“…It was due to the weak interfacial bonding between the chain in polysaccharides and microcrystalline cellulose, weakening the strength of the biocomposite film. The highest strength achieved in this study (5.060 MPa) with the addition of 7% NCC was higher than that reported by Ekielski et al [44] but was still lower than the one developed by Zhao et al [16]. This difference could be explained by the differences in the molecular weight, type of filler, and the fibre sources of the developed NCCs in this study.…”
Section: Mechanical Propertiescontrasting
confidence: 70%
“…It was due to the weak interfacial bonding between the chain in polysaccharides and microcrystalline cellulose, weakening the strength of the biocomposite film. The highest strength achieved in this study (5.060 MPa) with the addition of 7% NCC was higher than that reported by Ekielski et al [44] but was still lower than the one developed by Zhao et al [16]. This difference could be explained by the differences in the molecular weight, type of filler, and the fibre sources of the developed NCCs in this study.…”
Section: Mechanical Propertiescontrasting
confidence: 70%
“…The digestate can also be used in the industrial production of biocomposites. According to Ekielski et al (2021), the addition of digestate has a positive effect on improving the physical and mechanical parameters of some biocomposites, e.g., films (coatings) made of thermoplastic starch [32]. However, returning to the main use of digestate in agriculture, its real impact on soil properties and biomass yield is still untapped.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is worth adding that digestate sludge from an agricultural biogas plant can also be reused to produce biodegradable materials. Ekielski et al (2021) [10] showed that adding digestate to thermoplastic starch enabled the production of homogeneous biocomposites with a structure resembling a sheet or thick film. Furthermore, thermoplastic starch has emerged as a readily biodegradable and cheap biomaterial that can replace traditional plastics in applications such as food service and packaging [11].…”
Section: Introductionmentioning
confidence: 99%